Zranitelnost lékařské profese jako důsledek rostoucí autonomie pacientů - Glajchová, Alena (Lidé města, 2016)
In the context of the current health care system, patient autonomy is the main ethical principle in medicine, which emphasises respect for patients’ rights, their freedom of choice, and control of their own health. Presently, patients take a more active approach to their own health issues and seek medical information that is then used in their interaction with doctors. The new role of the patient as a client has been linked to increasing consumerism, and to the emergence of new possibilities, such as alternative medicine or self-treatment. However, their active role affects the formation of the doctor-patient relationship and the doctors’ expert position. Currently, the doctor-patient relationship is considered rather as a partnership, based on mutual cooperation, than a paternalistic relationship. Drawing on data from in-depth interviews with doctors, this article tries to understand how doctors perceive the new organisation of this relationship and the patients’ “new” knowledge of medicine. In particular, the aim is to show how doctors view patients who rely on information from the Internet and who take initiative in their interactions with doctors.